2021
DOI: 10.1111/os.13041
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Capsulotomy in Hip Arthroscopy: A Safe and Feasible Procedure for Cam‐Type Femoracetabular Impingement

Abstract: Objective To evaluate the surgical security, feasibility, and clinical efficacy of the longitudinal outside‐in capsulotomy in hip arthroscopic treatment for cam‐type femoracetabular impingement (FAI). Methods We retrospectively reviewed patients with cam‐type FAI who underwent hip arthroscopy in our institute from January 2018 to June 2019. All hip arthroscopic procedures were performed by one experienced surgeon in the same manner, except the fashions of capsulotomy. Fifty six patients with mean age of 39.1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The postoperative mHHS and VAS were both better than before surgery, and patient reported outcomes became better gradually with the time after surgery with no infection, neurapraxias, hip instability or revision appeared in all patients. In spite of the short follow-up time and no control group in this study, the modified longitudinal capsulotomy by outside-in approach was indicated to be a promising method in hip arthroscopy referencing the similar studies previously [ 6 , 7 ]. Moreover, the radiation exposure of surgeons and patients can be avoided because this method did not need intraoperative fluoroscopy.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…The postoperative mHHS and VAS were both better than before surgery, and patient reported outcomes became better gradually with the time after surgery with no infection, neurapraxias, hip instability or revision appeared in all patients. In spite of the short follow-up time and no control group in this study, the modified longitudinal capsulotomy by outside-in approach was indicated to be a promising method in hip arthroscopy referencing the similar studies previously [ 6 , 7 ]. Moreover, the radiation exposure of surgeons and patients can be avoided because this method did not need intraoperative fluoroscopy.…”
Section: Discussionsupporting
confidence: 70%
“…This approach took the place of puncture approach by seldinger technique in traditional hip arthroscopy. In recent years, studies of hip arthroscopy using the outside-in approach has increased gradually [ 4 , 7 , 8 , 9 , 10 , 11 ]. This approach can make the operation process quite easy for surgeons performing hip arthroscopy, and all surgical procedures can be achieved without special surgical instruments for hip arthroscopy, or the intraoperative fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations